2020
DOI: 10.1186/s12881-020-00995-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel electron transfer flavoprotein dehydrogenase (ETFDH) gene mutation identified in a newborn with glutaric acidemia type II: a case report of a Chinese family

Abstract: Background: Glutaric acidemia type II (GA II) or multiple acyl-CoA dehydrogenase deficiency (MADD, OMIM 231680) is an inherited autosomal recessive disease affecting fatty acid, amino acid and choline metabolism, due to mutations in one of three genes namely, electron transfer flavoprotein alpha-subunit, ETFA, electron transfer flavoprotein β-subunit, ETFB and electron transfer flavoprotein dehydrogenase, ETFDH. Currently, few studies have reported genetic profiling of neonatal-onset GA II. This study aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In our study, patient 4 with compound heterozygous variants, a frameshift mutation c.582_583insTA (p.P196T fs * 17) and a missense variant c.295C>T (p.R99C) had a relatively average age of onset and typical clinical picture of LOMADD. Nevertheless, previous reports reveal that patients with heterozygous frameshift and missense mutations appear to have an earlier age of onset than those with heterozygous missense mutations (32,(34)(35)(36)(37). Additionally, they frequently exhibit episodes of vomiting, drowsiness, appetite loss, asthenia, and acetonemic breath (32,(34)(35)(36)(37), none of which are prevalent in LOMADD.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, patient 4 with compound heterozygous variants, a frameshift mutation c.582_583insTA (p.P196T fs * 17) and a missense variant c.295C>T (p.R99C) had a relatively average age of onset and typical clinical picture of LOMADD. Nevertheless, previous reports reveal that patients with heterozygous frameshift and missense mutations appear to have an earlier age of onset than those with heterozygous missense mutations (32,(34)(35)(36)(37). Additionally, they frequently exhibit episodes of vomiting, drowsiness, appetite loss, asthenia, and acetonemic breath (32,(34)(35)(36)(37), none of which are prevalent in LOMADD.…”
Section: Discussionmentioning
confidence: 96%
“…MADD is a rare, potentially treatable β-oxidation disorder with three main subtypes: types I/II represent early onset in the neonatal period or infancy and type III represents the late onset of the disease [3,22].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have demonstrated that patients with MADD generally have mutations in ETFA, ETFB or ETFDH genes [ 11 , 12 , 13 ]. According to the Human Gene Mutation Database (HGMD), over 190 different variants of ETFDH have been reported so far and most of them are associated with the late-onset form of GA-II [ 14 , 15 , 16 ]. The majority of patients presented with the late-onset form are responsive to riboflavin therapy, but the molecular mechanism remains elusive.…”
Section: Introductionmentioning
confidence: 99%